Implementation of Surface Radiation and Fluid-Structure Thermal Coupling in Atmospheric Reentry - Ojas Joshi; Pénélope Leyland (International Journal of Aerospace Engineering)
During atmospheric reentry, radiative heating is one of the most important component of the total heat flux. In this paper, we investigate how the thermal radiation coming from the postshock region interacts with the spacecraft structure. A model that takes into account the radiation reflected by the surface is developed and implemented in a solid solver. A partitioned algorithm performs the coupling between the fluid and the solid thermal fields. Numerical simulation of a hollow cone head and a deployed flap region shows the effects of the radiative cooling and the significance of the surface radiation.